THE INFLUENCE OF SOCIAL MEDIA MARKETING STRATEGY ON PURCHASE INTENTION OF DEPOKFANTASYLAND TOURISM TICKETS MEDIATED BY BRAND AWARENESS - Dhea Nurmala Sari; Suci Ayu Sudari; Ali Ridho (ASIAN PUBLISHER, 2025)
This study aims to analyze the effect of social media marketing strategies on the purchase intention of tourism tickets to DepokFantasyLand, with brand awareness as a mediating variable. In today’s digital era, social media serves as a strategic promotional tool in the tourism sector. However, DepokFantasyLand still faces several challenges in building audience engagement and enhancing brand awareness, particularly on platforms such as Instagram and TikTok. This research employs a quantitative approach using the Structural Equation Modeling (SEM) method through the SmartPLS application. The sampling technique used is purposive sampling, involving a total of 100 respondents consisting of visitors or potential visitors who have encountered promotional content about DepokFantasyLand via social media. The results show that: (1) Social media marketing strategies significantly influence the improvement of brand awareness; (2) Brand awareness has a significant effect on the intention to purchase tourism tickets; and (3) Social media marketing strategies also have a significant indirect effect on purchase intention through brand awareness as a mediating variable. These findings affirm that optimizing digital marketing strategies plays a crucial role in attracting consumer interest and encouraging ticket purchase decisions.